2016
DOI: 10.12740/app/62154
|View full text |Cite
|
Sign up to set email alerts
|

Can meaning buffer work pressure? An exploratory study on styles of meaning in life and burnout in firefighters

Abstract: SummaryAim: The purpose of this study is to examine the relationships between different dimensions of meaning in life (personal meaning, the presence of meaning, a search for meaning) and burnout among firefighters. In addition, the differences in the level of burnout in firefighters were evaluated within the three of meaning in life.Method: Participants were 189 firefighters randomly recruited from 12 fire stations in southern Poland; they participated in the study voluntarily. The age range was 20-50 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
4
22
0
1
Order By: Relevance
“…These results are consistent with previous studies that have found meaning in life to be associated with less burnout in other professions (ie, firefighters) and to be associated with better overall psychological health and functioning. 14,15,24 Our findings support previous hypotheses that being aware of one's sense of meaning could be helpful for reducing stress. 9 Program directors in this sample reported lower levels of burnout (11%) compared to another study of practicing physicians (38%).…”
Section: Discussionsupporting
confidence: 87%
“…These results are consistent with previous studies that have found meaning in life to be associated with less burnout in other professions (ie, firefighters) and to be associated with better overall psychological health and functioning. 14,15,24 Our findings support previous hypotheses that being aware of one's sense of meaning could be helpful for reducing stress. 9 Program directors in this sample reported lower levels of burnout (11%) compared to another study of practicing physicians (38%).…”
Section: Discussionsupporting
confidence: 87%
“…But more than this, Frankl saw meaning as being one of the most important resources for coping with adversity: "There is nothing in the world, I would venture to say, that would so effectively help one to survive even the worst conditions as the knowledge that there is a meaning in one's life" ([1946] 1984:126). Consistent with the views of Frankl ([1946] 1984), findings from a number of studies suggest that a sense of meaning in life moderates the effects of stress on health (e.g., Haynes et al 2015;Krause 2007;Krause, Pargament, and Ironson 2017;Krok 2016).…”
Section: Meaning In Life As a Coping Resourcesupporting
confidence: 65%
“…Consistent with the views of Frankl ([] 1984), findings from a number of studies suggest that a sense of meaning in life moderates the effects of stress on health (e.g., Haynes et al. ; Krause ; Krause, Pargament, and Ironson ; Krok ).…”
Section: Introductionsupporting
confidence: 54%
“…The search for meaning in life was associated with higher negative affect, supporting H 2. Individuals who are seeking meaning may be less protected against an existentially demanding work environment and may be more prone to experiencing negative moods (Krok, ). The search for meaning in life was not associated with psychological distress, burnout or positive affect.…”
Section: Discussionmentioning
confidence: 99%